Factors influencing catalytic activity of Co-Zn double-metal cyanide complexes for alternating polymerization of epoxides and CO2 - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2015)
Co-Zn double-metal cyanides (DMCs) show good catalytic activity towards copolymerization of epoxides and CO2. A deep insight into the structural aspects of the catalysts that control their catalytic performance is addressed in this work. Method of preparation of DMC catalysts was found to have influence on their structure, which in turn dictated their catalytic activity. Complexing agent (t-BuOH) and density of strong acid sites of DMC catalysts were found critical factors responsible for their activity. Selectivity of DMC towards polycarbonates depends on the amount of alkali ion content in their composition. Induction period of the catalysts was governed by the strength of acid sites and by the presence of dispersed ZnCl2 in the composition. This study provides an understanding of the prime features of DMC catalysts that can be tuned for high productivity of polycarbonates. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: CO2 utilization; Copolymerization of epoxides and CO2; Double-metal cyanide; Polycarbonate